A systematic review of patient-reported outcome measures used to assess sleep in postpartum women using Consensus Based Standards for the Selection of Health Measurement Instruments (COSMIN) guidelines. Issue 10 (20th May 2021) - Sultan, P; Ando, K; Sultan, E; Hawkins, J; Blake, L; Barwick, F; Kawai, M; Carvalho, B
Abstract: Study Objectives: We performed a systematic review to identify the best patient-reported outcome measure (PROM) of postpartum sleep in women. Methods: We searched four databases for validated PROMs used to assess postpartum sleep. Studies were considered if they evaluated at least one psychometric measurement property of a PROM. An overall performance rating was assigned for each psychometric measurement property of each PROM based upon COSMIN criteria. A modified GRADE approach was used to assess the level of evidence and recommendations were then made for each PROM. Results: We identified 15 validation studies of eight PROMs, in 9, 070 postpartum women. An adequate number of sleep domains was assessed by five PROMs: Bergen Insomnia Scale (BIS), Pittsburgh Sleep Quality Index (PSQI), General Sleep Disturbance Scale (GSDS), Athens Insomnia Scale (AIS), and the Sleep Symptom Checklist (SSC). BIS and GSDS were the only PROMs to demonstrate adequate content validity and at least a low level of evidence of sufficient internal consistency, resulting in Class A recommendations. The BIS was the only PROM, which is easily accessible and free to use for noncommercial research, that achieved a Class A recommendation. Conclusion: The BIS is the best currently available PROM of postpartum sleep. However, this PROM fails to assess several important domains such as sleep duration (and efficiency), chronotype, sleep-disordered breathing and medication usage. Future studies should focus on evaluating the psychometric measurement properties of BIS in the North American setting and in different cultural groups, or to develop a more specific PROM of postpartum sleep.